(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Changes in the global climate pose a danger to plant growth and production and have a significant direct and indirect impact on the quantity and quality of plant nutrients. Combined with the rise in abiotic stresses, notably drought, developing nations are in urgent need of solutions that will maintain the production and nutritive value of their food crops. An essential food and oil crop for the world, groundnut supports agriculturally based livelihood methods that ensure food, nutrition, and financial security. Groundnut is an energy-dense food item and it contains a substantial amount of fat, proteins, and carbohydrates both fat soluble and water soluble vitamins, fibers, polyphenols, antioxidants, vitamins, and minerals. Due to the high nutrient contents of peanuts, they have been used to combat malnutrition in most developing countries.India is the second largest producer of groundnuts in the world, and the crop’s primary usage is for its oil. Peanuts are consumed in many forms such as boiled peanuts, peanut oil, peanut butter, roasted peanuts, and added peanut meal in snack food, energy bars, and candies.Drought causes substantial yield losses to groundnut production and adversely impacts nutritional quality.